2019
DOI: 10.1016/j.pscychresns.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate volume reductions in abstinent adolescent and young adult cannabis users: Association with affective processing deficits

Abstract: CONTRIBUTORS KEM was involved in data collection, developing the study concept, data processing, performing data analyses, interpreting the results, and writing the manuscript under KML's supervision. KML designed the study's methods and worked closely with KEM to develop the study concept, perform data analyses, interpret the results, and draft the manuscript. AMT was involved in data collection and data processing. MMK assisted in data collection, data processing, and preparation of the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 107 publications
3
18
1
Order By: Relevance
“…Of note, our sample underwent three-weeks of monitored abstinence from cannabis and other drugs of abuse before structural scans were conducted; thus, THC and other exogenous cannabinoids were metabolized out of the system [98], representing chronic rather than residual associations. These fronto-parietal cortical findings are consistent with several studies reporting abnormal brain morphometry in cannabis users, including reduced volume [21,23,24,99] and lesser cortical gyrification [36,37] in samples that were primarily male. These overall interactions did uncover SA abnormalities in the male cannabis users, which is inconsistent with prior null or marginal SA findings [37,40,100], however, future gender-stratified analyses are needed to ascertain gender-specific mechanisms in the relationship between cortical surface structure and cannabis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of note, our sample underwent three-weeks of monitored abstinence from cannabis and other drugs of abuse before structural scans were conducted; thus, THC and other exogenous cannabinoids were metabolized out of the system [98], representing chronic rather than residual associations. These fronto-parietal cortical findings are consistent with several studies reporting abnormal brain morphometry in cannabis users, including reduced volume [21,23,24,99] and lesser cortical gyrification [36,37] in samples that were primarily male. These overall interactions did uncover SA abnormalities in the male cannabis users, which is inconsistent with prior null or marginal SA findings [37,40,100], however, future gender-stratified analyses are needed to ascertain gender-specific mechanisms in the relationship between cortical surface structure and cannabis.…”
Section: Discussionsupporting
confidence: 90%
“…None of the prior studies examining these outcomes tested whether gender or aerobic fitness moderated these effects or controlled for aerobic fitness level. Although we found the relationship between cannabis use and cortical surface structure was moderated by two-way interactions which were observed between gender, cannabis and aerobic fitness in frontal, cingulate, and parietal regions; regions that have been found to be abnormal in previous studies [21,23,24,36,37,39]. Thus, we will focus on these novel interactions.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our brief neuropsychological battery did not include measures of psychomotor speed or visual learning and memory, which have also been shown to be impaired in cannabis users (Bolla, Brown, Eldreth, Tate, & Cadet, 2002;Lisdahl & Price, 2012;Wade, Wallace et al, 2019;Winward, Hanson, Tapert, & Brown, 2014). Furthermore, we did not conduct repeated neuroimaging and it is notable that previous studies have reported subtle deficits in brain function, connectivity, and structure following 2-4 weeks of monitored abstinence (Jacobus et al, 2012(Jacobus et al, , 2014Maple, Thomas, Kangiser, & Lisdahl, 2019;Price et al, 2015;Tapert et al, 2007); thus, additional longitudinal studies utilizing more sensitive measures of neuroimaging are needed before it can be concluded that full recovery is obtained following abstinence.…”
Section: Monitored Abstinence In Cannabis Usersmentioning
confidence: 99%
“…The purpose of the current study was to explore whether regular cannabis use in adolescents and young adults was associated with aberrant ifcMRI frontolimbic connectivity at rest. We employed a priori region of interest analysis focusing on regions with reported cortical differences between young cannabis users and controls, including: vmPFC (91, 92), ACC (81, 93, 94), insula (95), and amygdala (88, 96, 97). This project utilized ifcMRI data from three collection sites from the Imaging Data in Emerging Adults with Addiction (IDEAA) Consortium (University of Wisconsin-Milwaukee or UWM; McLean Hospital/Harvard University or McLean; University of Texas—Dallas or UTD).…”
Section: Introductionmentioning
confidence: 99%